IMPLEMENTASI AKUNTANSI ZAKAT DI LEMBAGA AMIL ZAKAT: TANTANGAN DAN PELUANG - Marwah Ibrahim; Azizah Zalfaa Salzabil; Nabiila Khonsaa Adefia; Mukhlishotul Jannah (Cahaya Ilmu Bangsa, 2024)
The implementation of PSAK 109 in zakat institutions will certainly experience opportunities and challenges that will be faced. This study aims to analyze the implementation of zakat accounting in zakat institutions and identify the challenges and opportunities that arise in the implementation of PSAK 109 accounting standards. With a case study method on zakat institutions, this study explores various aspects related to financial reporting and transparency faced in zakat management. The results of the study indicate that the implementation of PSAK 109 faces various challenges, such as regulatory issues, zakat management organization issues, mustahik and muzakki issues. However, opportunities to improve accountability and public trust are also open through the implementation of good standards. The recommendations in this study are expected to help zakat institutions overcome existing challenges and take advantage of opportunities in strengthening governance and transparency of financial reporting.